American Society of Regional Anesthesia and Pain Medicine expert panel recommendations on point-of-care ultrasound education and training for regional anesthesiologists and pain physicians—part II: recommendations. Issue 12 (24th February 2021) - Haskins, Stephen C; Bronshteyn, Yuriy; Perlas, Anahi; El-Boghdadly, Kariem; Zimmerman, Joshua; Silva, Marcos; Boretsky, Karen; Chan, Vincent; Kruisselbrink, Richelle; Byrne, Melissa; Hernandez, Nadia; Boublik, Jan; et al.
Abstract : Point-of-care ultrasound (POCUS) is a critical skill for all regional anesthesiologists and pain physicians to help diagnose relevant complications related to routine practice and guide perioperative management. In an effort to inform the regional anesthesia and pain community as well as address a need for structured education and training, the American Society of Regional Anesthesia and Pain Medicine Society (ASRA) commissioned this narrative review to provide recommendations for POCUS. The recommendations were written by content and educational experts and were approved by the guidelines committee and the Board of Directors of the ASRA. In part II of this two-part series, learning goals and objectives were identified and outlined for achieving competency in the use of POCUS, specifically, airway ultrasound, lung ultrasound, gastric ultrasound, the focus assessment with sonography for trauma exam, and focused cardiac ultrasound, in the perioperative and chronic pain setting. It also discusses barriers to POCUS education and training and proposes a list of educational resources. For each POCUS section, learning goals and specific skills were presented in the Indication, Acquisition, Interpretation, and Medical decision-making framework.